(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2022)
The avocado production has experienced a notable growth in recent years in Michoacán, consolidating itself as the main producer at the national level and one of the main exporters worldwide. However, marked disparities were observed between regions and municipalities in terms of productivity and performance levels. Given this scenario, there was a need to design strategies that would better exploit the productive potential of each area, compensating for limitations and promoting comparative advantages. The research aimed to address the question: How could a productive regionalization be designed to maximize the comparative advantages of each area in terms of surface area, yield, price, and productivity, compensating for their limitations and disparities, to optimize the global avocado production in Michoacán? The general objective was to propose a regionalization of avocado production in Michoacán, considering the productive disparities between regions. To achieve this, three specific objectives were outlined: to examine the evolution of indicators such as yield, harvested area, and rural average price of avocado in the main producing municipalities of Michoacán between 2010 and 2021; to compare the performance between these municipalities in the mentioned variables; and to identify possible explanatory factors of the productive leadership of some areas, considering comparative and competitive advantages. The methodology was based on a statistical analysis of the indicators using official data. Synthetic indicators were constructed, and regionalization techniques were applied to identify areas with homogeneous characteristics. The results allowed for the characterization of regions, identifying strengths, weaknesses, and opportunities for improvement. Differentiated strategies were defined by enhancing capacities, investing in lagging areas, and promoting regional complementarity. The proposal was an integral regionalization that, respecting productive vocations, allowed for the pooling of efforts and compensation of disparities to optimize the production of the Michoacán avocado sector.